ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR BERSIH KECAMATAN LEMBAR KABUPATEN LOMBOK BARAT: Analysis Of Clean Water Availability And Needs Lembar District, West Lombok District - Adriana, I Gde Sukanti; Yamin, Muhamad; Aminullah, Aminullah (Yayasan Al-Amin Qalbu, 2024)
The increasing population also reduces the quality of environmental sanitation. The need for clean water and environmental sanitation has become an international issue, namely in the 2015 Millennium Development Goal (MDG) where the need for clean water is a top priority. In this research, secondary data was taken at the PDAM Gerung West Lombok Branch office, data such as data on the number of house connections, water demand data and discharge data. This data is analyzed in the stages of calculating the projected number of house connections, calculating the need for clean water and calculating the projected discharge needed for the year, calculating the projected water loss until 2026, and calculating the water balance. After carrying out calculations by analyzing the data obtained from the relevant agencies, namely data from PDAM West Lombok Regency, it can be concluded that the water needs of thesheet subdistrict in 2024 = 2,547,851 m3/yr; in 2025 = 2,567,671 m3/yr and in 2026 = 2,687,370 m3/yr, the availability of water discharge in thesheet district in 2024 is = 2,860,937.25 m3/yr; in 2025 = 2,785,635.42 m3/yr; in 2026 it will be = 2,708,769.99 m3/yr, the water balance for thesheet subdistrict will decrease until in 2026 it will reach 21,399.99 m3/yr